2011
DOI: 10.1038/ajh.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Hypertension: The Interplay of Interleukin-6, Dietary Sodium, and the Renin-Angiotensin System in Humans

Abstract: Background Prior evidence suggests a link between inflammation and hypertension. Interleukin-6 (IL-6) has been implicated in animal studies to play an important role in angiotensin II (ANGII) mediated hypertension. The aim of this study was to examine the relationship of IL-6 and renin-angiotensin system (RAS) activity in human hypertension. Methods Data from 385 hypertensives and 196 normotensives are included in this report. Blood pressure and laboratory evaluation were performed on liberal and low sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 36 publications
5
87
1
3
Order By: Relevance
“…The restenosis is the arterial wall's healing response to mechanical injury and comprises two main processes, neointimal hyperplasia (i.e., smooth muscle migration/proliferation, extracellular matrix deposition) and vessel remodeling (Costa and Simon, 2005). In the literature, there has been evidence that the activation of the renin-angiotensin system (RAS) induces the production of pro-inflammatory cytokines, proliferation and vasoconstriction on the vasculature, and in consequence can contribute to initiation and progression of atherosclerosis (Chamarthi et al, 2011;Mehta and Griendling, 2007;van Thiel et al, 2015;Pacurari et al, 2014). In addition, RAS has been implicated in the pathogenesis of neointimal hyperplasia, and a role for angiotensin II in the migration and proliferation of vascular smooth muscle cells in restenosis has been reported (Pacurari et al, 2014;Valente et al, 2012;Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The restenosis is the arterial wall's healing response to mechanical injury and comprises two main processes, neointimal hyperplasia (i.e., smooth muscle migration/proliferation, extracellular matrix deposition) and vessel remodeling (Costa and Simon, 2005). In the literature, there has been evidence that the activation of the renin-angiotensin system (RAS) induces the production of pro-inflammatory cytokines, proliferation and vasoconstriction on the vasculature, and in consequence can contribute to initiation and progression of atherosclerosis (Chamarthi et al, 2011;Mehta and Griendling, 2007;van Thiel et al, 2015;Pacurari et al, 2014). In addition, RAS has been implicated in the pathogenesis of neointimal hyperplasia, and a role for angiotensin II in the migration and proliferation of vascular smooth muscle cells in restenosis has been reported (Pacurari et al, 2014;Valente et al, 2012;Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All of the established risk factors for cardiovascular disease, including hypertension (HTN) and hypercholesterolemia (HCh), are now recognized to induce a systemic inflammatory response that appears to underlie the vascular dysfunction that accompanies these conditions. Hypertensive patients exhibit elevated plasma levels of inflammatory mediators such as high-sensitive C-reactive protein, 1,2 interleukin 6 (IL-6), 2 interferon-inducible protein-10, and IL-4, IL-7, and IL-13. 3 Similarly, high-sensitive C-reactive protein, 4,5 chemokine CXC ligand 5 (CXCL5), 6 xanthine oxidase activity, IL-1 and IL-6 are all increased in plasma of HCh patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the present issue of American Journal of Hypertension, Chamarthi et al 5 further demonstrated a relationship between CRP, IL-6, and hypertension by comparing hypertensives to normotensives. The study also showed a significant rise in IL-6 in response to angiotensin II infusion in both hypertensives and normotensives.…”
mentioning
confidence: 81%